Integration of fisheries into marine spatial planning: Quo vadis?. (5th February 2018) - Janßen, Holger; Bastardie, Francois; Eero, Margit; Hamon, Katell G.; Hinrichsen, Hans-Harald; Marchal, Paul; Nielsen, J. Rasmus; Le Pape, Olivier; Schulze, Torsten; Simons, Sarah; Teal, Lorna R.; Tidd, Alex
Abstract: The relationship between fisheries and marine spatial planning (MSP) is still widely unsettled. While several scientific studies highlight the strong relation between fisheries and MSP, as well as ways in which fisheries could be included in MSP, the actual integration of fisheries into MSP often fails. In this article, we review the state of the art and latest progress in research on various challenges in the integration of fisheries into MSP. The reviewed studies address a wide range of integration challenges, starting with techniques to analyse where fishermen actually fish, assessing the drivers for fishermen's behaviour, seasonal dynamics and long-term spatial changes of commercial fish species under various anthropogenic pressures along their successive life stages, the effects of spatial competition on fisheries and projections on those spaces that might become important fishing areas in the future, and finally, examining how fisheries could benefit from MSP. This paper gives an overview of the latest developments on concepts, tools, and methods. It becomes apparent that the spatial and temporal dynamics of fish and fisheries, as well as the definition of spatial preferences, remain major challenges, but that an integration of fisheries is already possible today.